128PTislelizumab in combination with chemotherapy for Chinese patients (Pts) with gastric/gastroesophageal junction cancer (GC/GEJC) or esophageal squamous cell carcinoma (ESCC). (24th November 2019) - Bai, Y; Xu, N; Yuan, X; Wang, B; Li, E; Li, X; Li, Y; Wang, X; Yang, S; Xu, J
Abstract: Background: Tislelizumab, an investigational monoclonal antibody with high affinity and specificity for PD-1, was engineered to minimize binding to FcγR on macrophages in order to abrogate antibody-dependent phagocytosis, a mechanism of T-cell clearance and potential resistance to anti-PD-1 therapy. In prior reports, tislelizumab, as a single agent and in combination with various chemotherapies, was generally well tolerated and had antitumor activity in pts with advanced solid tumors. This phase 2 study (NCT03469557) assessed tislelizumab plus chemotherapy as first-line therapy in pts with inoperable, locally advanced, or metastatic GC/GEJC or ESCC. Methods: Patients with GC/GEJC received tislelizumab (200 mg IV Q3W) + oxaliplatin (130 mg/m 2 IV Q3W for ≤6 cycles) and capecitabine (1000 mg/m 2, Days 1-15 orally BID Q3W); pts with ESCC received tislelizumab + cisplatin (80 mg/m 2 IV Q3W for ≤6 cycles) and 5FU (800 mg/m 2 /d, Days 1-5 IV Q3W for ≤6 cycles). Response was assessed using RECIST v1.1, Kaplan-Meier analysis estimated survival, and adverse event (AE) monitoring examined safety/tolerability. Results: As of 31 Mar 2019, 30 pts with GC/GEJC and ESCC (n = 15 each) were enrolled. Median age was 61 yr; most pts were male (n = 25). Clinical responses were observed during treatment (Table). In pts with ESCC, treatment-emergent AEs (TEAEs) of grade ≥3 occurring in ≥ 2 pts were vomiting and dysphagia (n = 4 each), hyponatremia (n = 3), and anemia, leukopenia, fatigue, lung infection, and decreased weight (n = 2 each). No grade ≥3 TEAEs occurred in ≥ 2 pts with GC/GEJC. One pt with ESCC had a fatal AE (hepatic dysfunction) attributed to treatment by the investigator, but which may have been confounded by progressive disease and underlying hepatitis. Conclusions: Tislelizumab plus chemotherapy was generally well tolerated and antitumor activity was observed in pts with advanced GC/GEJC or ESCC. Clinical trial identification: NCT03469557. Editorial acknowledgement: Writing and editorial support for this abstract was provided by Agnieszka Laskowski, PhD, and Elizabeth Hermans, PhD, of OPEN Health Medical Communications (Chicago, IL). Legal entity responsible for the study: BeiGene Co., Ltd., Beijing, China. Funding: BeiGene (Beijing) Co., Ltd., Beijing, China. Disclosure: X. Li: Full / Part-time employment: BeiGene (Beijing) Co., Ltd. Y. Li: Full / Part-time employment: BeiGene (Beijing) Co., Ltd. X. Wang: Full / Part-time employment: BeiGene (Beijing) Co., Ltd. S. Yang: Full / Part-time employment: BeiGene (Beijing) Co., Ltd. All other authors have declared no conflicts of interest.